PENGARUH PERSEPSI PELAYANAN PEGAWAI PAJAK, PENGETAHUAN FRAUD WAJIB PAJAK DAN TIMBAL BALIK PEMERINTAH TERHADAP KEPATUHAN PAJAK OLEH WAJIB PAJAK (Studi pada wajib pajak orang pribadi Kabupaten Demak) - Sukanto, Eman; Nafiah, Alif (STIE AUB Surakarta, 2018)
This study measures the influence of perceptions of employee tax services, taxpayer knowledge about fraud and reciprocal government tax compliance by taxpayers in KabupatenÂ Demak. Sample in this research as many as 100 people taxpayer personal cross profession registered in KPP Demak. This study used questionnaire instrument. This research concludes, firstly, the perception of service tax officers have a positive effect on tax compliance, which means the better served, taxpayers more obedient. Second, the knowledge of fraud has an effect on tax compliance, meaning that the taxpayer understands about cheating and the consequences of fraud, they are more obedient. Third, the reciprocal government does not affect taxpayer compliance, meaning that taxpayers will remain obedient to pay taxes even if they do not get reciprocity.Keywords: Tax Service, Fraud Knowledge, Government Reciprocity, Tax Compliance